Epigenetic Age Acceleration and Cognitive Decline: A Twin Study. (19th February 2021) - Vaccarino, Viola; Huang, Minxuan; Wang, Zeyuan; Hui, Qin; Shah, Amit J; Goldberg, Jack; Smith, Nicholas; Kaseer, Belal; Murrah, Nancy; Levantsevych, Oleksiy M; Shallenberger, Lucy; Driggers, Emily; et al.
Abstract: Background: Little is known about the role of DNA methylation (DNAm) epigenetic age acceleration in cognitive decline. Using a twin study design, we examined whether DNAm age acceleration is related to cognitive decline measured longitudinally in persons without a clinical diagnosis of dementia. Methods: We studied 266 paired male twins (133 pairs) with a mean age of 56 years at baseline. Of these, 114 paired twins returned for a follow-up after an average of 11.5 years. We obtained 6 indices of DNAm age acceleration based on epigenome-wide data from peripheral blood lymphocytes. At both baseline and follow-up, we administered a battery of cognitive measures and constructed 2 composite scores, one for executive function and one for memory function. We fitted multivariable mixed regression models to examine the association of DNAm age acceleration markers with cognitive function within pairs. Results: In cross-sectional analyses at baseline, there was no association between DNAm age acceleration and cognitive function scores. In longitudinal analyses, however, comparing twins within pairs, each additional year of age acceleration using the Horvath's method was associated with a 3% decline (95% CI, 1%–5%) in the composite executive function score and a 2.5% decline (95% CI, 0.01%–4.9%) in the memory function score. These results did not attenuate after adjusting for education and other risk factors. Conclusions: Middle-aged men who had older DNAm age relative to their brothers of the same demographic age showed a faster rate of cognitive decline in the subsequent 11.5 years. These results point to the role of epigenetic modifications in cognitive aging.